Relasi Pemahaman Keagamaan dan Etika Lingkungan: Perilaku Green Campus di Ma’had al-Jami’ah PTKIN Indonesia - Bambang Ruswandi; Irfan Mas’ud Abdillah; Fatihunnada; Farita Putri Indriyani; Rizka Venusia Budyati (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2025)
This study revisits the relationship between students’ religious understanding and their Green Campus behavior, addressing previous findings by scholars such as Hakim, Rohman, Boyes, and Gabriela, who reported no significant influence. Employing a quantitative approach with Structural Equation Modeling (SEM)—Partial Least Square, the research involves 250 Ma’had al-Jami’ah students from four PTKIN institutions: UIN Jakarta, UIN Bandung, UIN Semarang, and UIN Surabaya. Quota sampling was used to select respondents. Findings show that the students’ level of religious understanding is relatively low, with an overall index of 48.62. The four indicators contributing to this score are religious practice (59.19), religious consequences (57.70), religious knowledge (53.05), and religious experience (76.45). In contrast, their Green Campus behavior is categorized as fairly good, with an index of 50.86, measured through environmentally friendly consumption (63.96), recycling (54.41), transportation (67.25), waste reduction (63.71), and energy conservation (80.92). Hypothesis testing reveals a significant and positive effect of religious understanding on Green Campus behavior, accounting for 42.1% of the variance. These results indicate that higher levels of religious understanding are associated with stronger Green Campus behavior. The study thus challenges earlier findings and highlights the relevance of religious understanding in shaping environmentally responsible actions among Ma’had al-Jami’ah students. It also contains ethical–philosophical implications that religious teachings function as a moral foundation and ethical consciousness in fostering ecological responsibility within Islamic higher education institutions.